2017
DOI: 10.1021/acs.iecr.7b01015
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Pair Formation Constants of Lithium Borate and Lithium Hydroxide under Pressurized Water Nuclear Reactor Coolant Conditions

Abstract: A custom-made high-precision flow AC conductance instrument was used to measure the frequency-dependent molar electrical conductivities of aqueous solutions of lithium borate from T = 298 K to T = 548 K at a constant pressure, p = 20 MPa. Ion-pair formation constants of lithium borate, K A,m [LiB(OH) 4 0 ], were derived from these measurements using the Turq− Blum−Bernard−Kunz (TBBK) conductivity model. Our results are consistent with previous low-temperature studies and are the first to be reported at tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 53 publications
4
21
0
Order By: Relevance
“…The MULTEQ model uses the Marshall and Franck expression for K w , while the OLI model is based on the treatment by Tanger and Helgeson . The impact of the formulation used for K w is discussed in more detail in our recent lithium borate study …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MULTEQ model uses the Marshall and Franck expression for K w , while the OLI model is based on the treatment by Tanger and Helgeson . The impact of the formulation used for K w is discussed in more detail in our recent lithium borate study …”
Section: Discussionmentioning
confidence: 99%
“…34 The impact of the formulation used for K w is discussed in more detail in our recent lithium borate study. 37…”
Section: Discussionmentioning
confidence: 99%
“…The TBBK Model. The concentration dependence of the solution conductivity was modeled with the same data treatment strategy used in previous work on ion association in metal borate solutions, 9,10 in which the TBBK model 20 was used together with the mixing rule reported by Sharygin et al 22…”
Section: Tbbk Conductivity Data Analysismentioning
confidence: 99%
“…In 2000, Palmer re-evaluated the literature data for borate and polyborates and developed expressions for the formation constants as functions of solvent density, temperature, and ionic strength. More recent work in our laboratory reported accurate ionization constants of boric acid and ion-pair formation constants of alkali metal borates from 298 to 623 K. , Our work on alkali metal borates included the determination of temperature-dependent values for the limiting conductivity of borate. No accurate values for the limiting conductivities of polyborates have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, at least five types of borate species, [B(OH) 3 ], [B(OH) 4 − ], [B 3 O 3 (OH) 4 − ], [B 4 O 5 (OH) 4 2− ], and [B 5 O 6 (OH) 4 − ], have been found in solution, and the amount of them varies with environmental conditions. In recent years, studies have shown that many factors, such as pH, counter‐ions, temperature, and equilibrium time, affect transformations among borate ions in solution. The borate species have a higher level of hydration and hydrolysis in dilute solution, where high‐polymerization borate anions hydrolyze into low‐polymerization borate anions, such as [B(OH) 3 ] and [B(OH) 4 − ].…”
Section: Introductionmentioning
confidence: 99%